Macular thickness measurements in healthy eyes using six different optical coherence tomography instruments - Wolf-Schnurrbusch, Ute E K; Ceklic, Lala; Brinkmann, Christian K; Iliev, Milko E; Frey, Manuel; Rothenbuehler, Simon P; Enzmann, Volker; Wolf, Sebastian (Investigative ophthalmology & visual science, 2009)
To compare central retinal thickness (CRT) measurements in healthy eyes by different commercially available OCT instruments and to compare the intersession reproducibility of such measurements. Six different OCT instruments (Stratus OCT [Carl Zeiss Meditec, Inc. Dublin, CA], SOCT Copernicus [Reichert/Optopol Technology, Inc., Depew, NY], Spectral OCT/SLO [Opko/OTI, Inc., Miami, FL], RTVue-100 [Optovue Corp., Fremont, CA], Spectralis HRA+OCT [Heidelberg Engineering, Inc., Heidelberg, Germany], and Cirrus HD-OCT [Carl Zeiss Meditec, Inc.]) were used to assess CRT in both eyes of healthy subjects. Measurements were performed in two different sessions on the same day with each of the systems. From these measurements, the mean CRT was calculated. For the assessment of the intersession reproducibility of the instruments, we calculated the coefficient of the variation of test-retest variation. Twenty healthy subjects were included in the study. Compared with the Stratus OCT all spectral OCT instruments showed significantly higher CRTs. The Spectralis HRA+OCT and Cirrus HD-OCT showed similar CRT values but significantly higher values than did all other instruments. The coefficients of variation for repeated measurements was 3.33% for the Stratus OCT, 0.46% for the Spectralis HRA+OCT, 3.09% for the Cirrus HD-OCT, 2.23% for the OCT/SLO, 2.77% for the RTVue-100 OCT, and for the SOCT 3.5%, respectively. discussion. The six OCT systems provided different results for CRT. The measurements with the Stratus OCT showed the lowest thicknesses, whereas those with the Cirrus HD-OCT and Spectralis HRA+OCT yielded the highest ones. These discrepancies can be explained by the differences in the retinal segmentation algorithms used by the various OCT systems. Whereas the Spectralis HRA+OCT and Cirrus HD-OCT include the RPE layer in the retinal segmentation, the other instruments do not. The data imply that the different OCT systems cannot be used interchangeably for the measurement of macular thickness.